HUBUNGAN PENGETAHUAN, SIKAP DAN LINGKUNGAN PETANI KOPI TENTANG ALAT PELINDUNG DIRI (APD) DALAM PENGGUNAAN PESTISIDA DI WILAYAH KERJA PUSKESMAS LAMPAHAN KECAMATAN TIMANG GAJAH KABUPATEN BENER MERIAH TAHUN 2024 - Syahraini, Nadila; Saipullah; Alamsyah, Sanjaya (Jurnal Ilmiah Cerebral Medika, 2025)
ABSTRACT Knowledge, Attitudes, and Environmental Factors of Coffee Farmers Regarding Personal Protective Equipment (PPE) in Pesticide UseThe general objective of this study is to determine the relationship between the knowledge, attitudes, and environmental factors of coffee farmers regarding Personal Protective Equipment (PPE) in pesticide use within the working area of Lampahan Health Center, Timang Gajah District, Bener Meriah Regency, in 2024. This research is a quantitative study with a cross-sectional approach. The population of this study consists of heads of households using pesticides, totaling 330 farmers. The sample size for the study is 76 farmers, and sampling was conducted using Accidental Sampling. The research instrument used is a questionnaire. Data analysis methods include univariate and bivariate analyses using the chi-square test. The results of the study show that the farmers' level of knowledge is adequate, reaching 60,5% or 46 farmers. The farmers' attitudes are adequate at 61.8% or 47 farmers. The influence of the farmers' environment is also adequate, with 56.6% or 43 farmers. The usage of Personal Protective Equipment (PPE) by farmers is adequate at 52.6% or 40 farmers. Based on the chi-square test results, the knowledge variable has a p-value of 0.087, which is greater than 0.05, indicating that there is no significant relationship between knowledge and PPE use. The attitude variable has a p-value of 0.00, which is less than or equal to 0.05, indicating a significant relationship between attitude and PPE use. The environmental influence variable also has a p-value of 0.00, indicating a significant relationship between environmental influence and PPE use. Recommendations include enhancing understanding and awareness of the importance of using Personal Protective Equipment (PPE) properly during pesticide mixing and spraying, and overcoming the discomfort associated with PPE use during pesticide application. Keywords : Knowledge, Attitudes, Environment, Farmers, PPE, Pesticides